PENGARUH KEPEMILIKAN INSTITUSIONAL, LEVERAGE, PROFITABILITAS, DAN KUALITAS LAPORAN KEUANGAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA SUB SEKTOR MAKANAN DAN MINUMAN DI BEI PERIODE 2020-2024) - Tesalonika Tesalonika; Anissa Amalya Mulya (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The study examines the influence of institutional ownership, leverage, profitability, and financial reporting quality on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. A quantitative approach is employed, using a purposive sampling technique, resulting in a sample of 50 companies. The sampling criteria include: listed on the IDX until 2024; conducted their IPOs before 2020 and remained continuously listed throughout 2020-2024; published complete annual financial statements for the entire period; and had available year-end stock price data from 2020-2024. Secondary data were obtained from the official IDX website and analyzed using the SPSS program. The results show that institutional ownership and financial reporting quality do not have a significant effect on firm value. In contrast, leverage has a significant positive effect, while profitability has a significant negative effect on firm value.